PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN POWTOON TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI STATISTIKA KELAS VIII - Werdhaty, Wella Triayu; Astuti, Reni; Irvandi, Wandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the validity, practicality and effectiveness of powtoon-assisted learning media on problem-solving abilities in statistics material for class VIII at SMP Negeri 10 Sungai Kakap. The research method used is research and development (R&D). The results of the study showed that the learning media developed met the criteria of very valid with a percentage of material expert validity of 86.67% and media expert validity of 92.38%. The practicality of the media reached the criteria of very practical with the results of the student response questionnaire of 87.14% and the teacher response questionnaire obtained a percentage of 98.82%. The effectiveness of the media reached the criteria of effective with an average of students getting a score of 71.43% based on the KKM value determined at the school so that it can be concluded that powtoon-assisted learning media can improve students' problem-solving abilities.